ANALISIS PENGARUH BENTUK MODEL TRANSOM DAN SKEG KAPAL PADA TONGKANG TERHADAP HAMBATAN SERTA SEAKEEPING MENGGUNAKAN METODE CFD - Drajat Satrio Wibowo (2023)
Skeg and transom are parts of the barge located at the stern. In some cases there are barges that are difficult to operate. In this study, the aim was to determine the effect of the transom and skeg on the resistance and RAO given by the ship. As for the research variation model on skeg with angles of 180˚, 150˚ and 130˚. As for the transom, the transom is above the waterline and below the waterline. To get the resistance is done by simulation using Ansys Fluent software, while to get the ship's RAO against waves using Ansys Aqwa software. The simulations carried out show that a barge with skeg that forms an angle will increase the resistance value, the smaller the angle formed, the greater the resulting resistance. The transom that is below the waterline also adds to the resistance it generates. The RAO of the barge against waves is also affected by the skeg angle. Skegs with an angle of 130˚ have a better RAO than skegs of 150˚ and 180˚. Even though it has the lowest RAO, barges with skeg 130˚ have the greatest resistance so to optimize the resistance and RAO, skeg 150˚ can be considered.